Strangulated Spigel hernia - Fronzutti, Agustín; Armand Ugón, Alfredo; Zeballos, Elbio (Cirugía del Uruguay, 1977)
The author had a patient with strangled spigelian hernia, and so proceeded to review existing case material. Anatomy, etiology and incidence of this condition are discussed in this paper, with emphasis in the difficulties for estableshing diagnosis of this type of abdominal herniation.